Ethanol Enhances High-Salinity Stress Tolerance by Detoxifying Reactive Oxygen Species in Arabidopsis thaliana and Rice - Nguyen, Huong Mai; Sako, Kaori; Matsui, Akihiro; Suzuki, Yuya; Mostofa, Mohammad Golam; Ha, Chien Van; Tanaka, Maho; Tran, Lam-Son Phan; Habu, Yoshiki; Seki, Motoaki (Frontiers in Plant Science, 2017)
High-salinity stress considerably affects plant growth and crop yield. Thus, developing techniques to enhance high-salinity stress tolerance in plants is important. In this study, we revealed that ethanol enhances high-salinity stress tolerance in Arabidopsis thaliana and rice. To elucidate the molecular mechanism underlying the ethanol-induced tolerance, we performed microarray analyses using A. thaliana seedlings. Our data indicated that the expression levels of 1,323 and 1,293 genes were upregulated by ethanol in the presence and absence of NaCl, respectively. The expression of reactive oxygen species (ROS) signaling-related genes associated with high-salinity tolerance was upregulated by ethanol under salt stress conditions. Some of these genes encoded ROS scavengers and transcription factors (e.g., AtZAT10 and AtZAT12). A RT-qPCR reaction analysis confirmed that the expression levels of AtZAT10 and AtZAT12 as well as AtAPX1 and AtAPX2, which encode cytosolic ascorbate peroxidases (APX), were higher in ethanol-treated plants than in untreated control plants, when exposure to high-salinity stress. Additionally, A. thaliana cytosolic APX activity increased by ethanol in response to salinity stress. Moreover, histochemical analyses with 3,3′-diaminobenzidine (DAB) and nitro blue tetrazolium (NBT) revealed that ROS accumulation was inhibited by ethanol under salt stress conditions in A. thaliana and rice, in which DAB staining data was further confirmed by hydrogen peroxide contents. These results suggest that ethanol enhances high-salinity stress tolerance by detoxifying ROS. Our findings may have implications for improving salt-stress tolerance of agriculturally important field-grown crops.